Augmented Reality-Based Student Worksheet to Stimulate Students’ Critical Thinking Skills - Fendi, Romy Desmara; Suyatna, Agus; Abdurrahman, Abdurrahman (Universitas Islam Negeri Raden Intan Lampung, 2021)
Critical thinking skill which is one of the important abilities in the 21st century is important to be trained in learning. The purpose of this research is to develop an AR-based worksheet on dynamic electrical material that is valid, practical, and effective to stimulate students’ critical thinking. The development model used the ADDIE model which consists of analysis, design, development, implementation, and evaluation steps. The product developed was tested for validation, practicality test, and effectiveness test. The results of the validity test obtained a value of 81.80% with a valid category. The results of the practicality test obtained a percentage of 80.85% with good criteria. The results of the effectiveness test showed an N-Gain value of 0.67 with the moderately effective category. From the average pretest and posttest scores, it can be seen that the posttest average score increased by 39.04 which indicates that the use of AR-based worksheets can improve students’ critical thinking. It can be concluded that AR-based worksheets on the concept of dynamic electricity developed are valid, practical, and effective to stimulate students’ critical thinking.